KEWENANGAN BUPATI DALAM PEMBANGUNAN INFRASTRUKTUR (STUDI PENELITIAN PEMBANGUNAN JALAN DESA SUNGAI PINANG II, KABUPATEN OGAN ILIR, SUMATERA SELATAN) - Grace Garatama M; Wiratno (Reformasi Hukum Trisakti, 2023)
The development of road infrastructure supports the economic and social development of a region. This research raises the problem of how the Regent's authority is implemented in carrying out the construction of the Sungai Pinang II village road infrastructure in Ogan Ilir Regency in 2016-2021 and what obstacles the Regent experienced in carrying out the construction of the Sungai Pinang II village road infrastructure in Ogan Ilir Regency in 2016-2021 and what is the solution. The research method is normative research and regulatory approach. The results and discussion are that the implementation of the Regent's authority in implementing the construction of Sungai Pinang II village road infrastructure in Ogan Ilir Regency for 2016-2021 as regulated and in Regional Regulation Number 4 of 2021 concerning RPJMD for Ogan Ilir Regency for 2021-2026 has not been realized completely and perfectly.  The obstacles experienced by the Regent in road construction in Ogan Ilir Regency are related to limited financial capacity and limited characteristics of regional expenditure allocations. The conclusion of this research is that the Regent of Ogan Ilir, through his authority to carry out development based on the RPJMD, has not been able to realize and overcome road construction obstacles properly.